Performance evaluation of flexible cross correlation (FCC) OCDMA code based on radio over fiber (RoF) simulation system - Z. Ibrahim; C.B.M. Rashidi; S.A. Aljunaid; A.K. Rahman; M.S. Anuar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper investigates the performance of an elegance code set algorithm known as Flexible Cross Correlation (FCC) code to be run into a simulation test of proposed RoF system. Executing OCDMA Code into RoF framework is seen as a promising technique for enhancing spectral efficiency and meanwhile enhanced the length of fiber optic cable and data bit rate execution while reduce the passive equipment device. This code can efficaciously reduce the results of phase-induced intensity noise (PIIN), it has the multiple access interference (MAI) cancellation belongs to RoF system and at the same time simple and easy within the code construction. Bit error rate (BER) performance is assessed for this proposed simulation system. The evaluation made based on the performance of fiber length, data bit rate, related with Bit Error Rate (BER) and also the complexity of the system. The extensive simulation results reveal FCC code possibly will accomplish sufficiently up to 51 km at BER 10-9 for data rate 155 Mbps as matched to 622 Mbps with exponentially increases at BER 10-12 error floor and it is fit for short haul networking such as FTTH and local area network (LAN).